efectuati:
9×{[8+7×(6+5)]×4-3}+2
urgent!!!
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
9×[(8+7×11)×4-3]+2=
9×[(8+77)×4-3]+2=
9×(85×4-3)+2=
9×(340-3)+2=
9×337+2=
3033+2=
3035
andreea12577:
multumesc!
Răspuns de
1
Răspuns:
9 × [( 8 + 7 × (6 + 5) × 4 - 3] + 2 = 7607
9 × ( 8 + 7 × 30 × 4 - 3) + 2 =
9 × ( 8 + 210 × 4 - 3 ) + 2 =
9 × ( 8 + 840 - 3) + 2 =
9 × ( 848 - 3 ) + 2 =
9 × 845 + 2 =
7605 + 2 = 7607
Alte întrebări interesante
Matematică,
8 ani în urmă
Biologie,
8 ani în urmă
Istorie,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă